Analisis Genetik Pada Ayam Lokal Untuk Mendukung Program Pemuliaan Ternak Nasional - Putramaalkairi (Jurnal Ilmu Peternakan Indonesia, 2025)
Local chickens in Indonesia possess significant genetic potential to be developed in support of national food security. However, their productivity needs improvement through effective and sustainable breeding programs. This study aims to analyze the genetic diversity and population structure of local chickens from three different regions using microsatellite (SSR) markers as a basis for breeding program development. Blood samples from 150 local chickens were collected, and DNA was isolated and analyzed using PCR and electrophoresis techniques to identify genetic variation. Results showed an average heterozygosity of 0.65 and a genetic differentiation among populations with an Fst value of 0.12, indicating considerable genetic diversity and a fragmented population structure. Genetic analysis also revealed associations between genetic markers and important phenotypic traits such as body weight and egg production, as well as potential adaptation to extreme environmental conditions. These findings highlight the importance of molecular technology utilization in local chicken breeding programs to enhance productivity while maintaining adaptive traits. The study recommends the development of marker-assisted selection and genetic resource conservation as key strategies to support the national livestock breeding program.